Semantic preference and semantic prosody of the collocations of sustainable in NOW corpus - Hardiman, Denitha Putri; Nuraniwati, Tri (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sustainability has dominated the conversation about climate change since the early 2000s. The presence of Sustainable Development Goals strengthened the connection between the two (SDGs) set up by the United Nations General Assembly in 2015, with Goal Number 13 being climate action concerning the ever-worsening climate change. Ever since the word ‘sustainable’ has been heavily circulated in the media, it has been associated with various words from fashion to finance. Utilising the News on the Web (NOW) Corpus, the study explores the representation of the word ‘sustainable’ in media concerning climate change discussion under semantic prosody and semantic preference analysis. Using collocations of the node word, semantic preference determines the semantic set related to the node word, while semantic prosody interprets the environment in which the node word pertains. The collocations are semantically labelled with the help of an automatic semantic tagger UCREL Semantic Analysis System (USAS) to find the semantic preference. At the same time, the concordance lines in NOW Corpus are examined to determine the semantic prosody. The study finds that the word ‘sustainable’ tends to be associated with semantic sets related to the environment, Sustainable Development Goals, social issues and humanity, as well as money. It also indicates that the node word has positive prosody. The representation of the word ‘sustainable’ in the media is seen as favourable, not only as a way of living but also as a way of behaving in many aspects encompassing our lives.